Essays on the economics of groundwater depletion and management in irrigated agriculture - Perez-Quesada, Gabriela (Kansas State University, 2022)
The depletion of groundwater stocks reduces the flow of economic value and the production of goods from the resource. This dissertation quantifies these effects in the context of the High Plains Aquifer in the central US. One particular challenge in estimating these effects that we overcome is that feedback effects from irrigation behavior affect resource conditions, which creates an endogeneity concern. We also provide new insights on the potential of collective efforts by irrigators to manage the resource. We study how heterogeneity in resource and user characteristics affect their individuals' willingness to support efforts to collectively reduce water use. The first chapter estimates how changes in groundwater stocks affect the returns to agricultural land. We avoid bias from feedback effects by exploiting hydrologic variation in pre-development saturated thickness that was determined by natural processes in previous geological eras. Simulation results reveal that the average annual present value of returns to land are expected to decrease in the High Plains region by $120.6 million in 2050, and by $250.5 million in 2100. The most severe decreases in returns to land are expected to occur in Texas, Kansas, and Colorado. When the initial saturated thickness is less than 70 feet, most of the economic impact (63%) of a decrease in the stock of groundwater occurs through an adjustment in irrigated acreage (extensive margin), while 37% occurs through reduced irrigated rental rates (intensive margin). When saturated thickness is larger, nearly all of the response is at the extensive margin. The second chapter examines how observed differences in the stock of groundwater affect corn production. To account for the endogeneity of groundwater stock, we exploit variation in current saturated thickness due to variation in pre-development saturated thickness. Simulation results reveal that the annual production of corn would decrease by 48.1 million bushels in the north portion of the High Plains Aquifer due to a uniform 10 ft decrease in saturated thickness, whereas the annual production of corn would decrease by 15.7 million bushels in the south. Further, we find that when initial saturated thickness is less than 70 ft, most of the impact on corn production of a decrease in the stock of groundwater occurs through an adjustment in irrigated acres in both the north and the south. When saturated thickness is larger than 70 ft, then the adjustment is mostly through a change in cropping patterns on irrigated land in the south but still through irrigated acres in the north. The third chapter uses unique data obtained from consequential stated preference surveys in Kansas to explore the factors that influence farmers preferred reductions in groundwater use through a water conservation program implemented by a Groundwater Management District. Our results reveal that farmers located in areas where the aquifer is more depleted support larger reductions in groundwater use. But we also find that characteristics of the users matter as much or more than the status of the aquifer in determining support. Opposition to reductions in water use are strongest among farmers who strongly agree that water rights are a private property, landlords and those who irrigate a larger proportion of their farm. Further, we evaluate farmers' preferences for the methods of assigning water allocations. We find that none of the options are preferred by a majority of farmers and there is no clear evidence that aquifer characteristics or observed farmer characteristics are the key factors affecting the probability that a farmer ranks a method as the best option. This makes it difficult for groundwater managers to identify which method is more likely to be considered fair by farmers. Our results are informative for managers of water throughout Kansas, the High Plains and other regions where conserving water resources is a high priority and localized and stakeholder-driven conservation plans could be a solution.
Keywords: Groundwater; Depletion; Irrigation; Feedback effects; Local management